Pengaruh Kompetensi, Budaya Organisasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan - Annisa Siregar (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of competence, organizational culture, and work discipline on the performance of employees of PT Sido Muncul, either partially or simultaneously. Data collection was carried out by distributing questionnaires via Google Form to 131 respondents who were employees of PT Sido Muncul. By using a Likert scale. Respondents' answers were processed by multiple regression analysis, t-test, F-test and R-2 test. The results of this study found that there was a significant (significant) effect partially between competency, organizational culture, and work discipline variables on the performance of employees of PT Sido Muncul. In addition, the results of this study also found that there was a significant (significant) effect simultaneously on both competency, organizational culture, and work discipline variables on the performance of PT Sido Muncul employees.